Quantification of Electronic Activity Inside Photo-Activated TiO2 Layers through a New Electrical Model Supported by Electrokinetic Data. Issue 16 (1st January 2019) - Gallardo-Moreno, Amparo M.; Romero-Guzmán, Daniel; González-Martín, M. Luisa
Abstract : Surface electrical characterization of metals and semiconductors with extensive geometry continues to be of interest. This work explores the electrical information that can be extracted from the electrokinetic (zeta) potential of metallic surfaces, and proposes an analytical model based on streaming potential/current data. In particular, our study focuses on the alloy Ti6Al4V, which is capable of modifying its surface electrical properties after excitation with ultraviolet irradiation due to the semiconductor properties of its TiO2 passivation layer. Evidence is presented for the first time of electronic activity inside the passivation layer following UV excitation. Charge displaced through sample (Q), electrons density (evol ), surface charge density (σ) and current density (J) are extracted from the proposed model. The amount of displaced charge through Ti6Al4V disks not exposed to UV irradiation was similar to that displaced inside the thin TiO2 excited layer. Relative conductivity of the TiO2 excited layer versus Ti6Al4V showed a difference of up to five orders of magnitude between the two samples. The model is suitable for application to any metal and any excited semiconductor, thus increasing the usefulness of electrokinetic characterization based on streaming potential/current measurements.